Reflection Characteristics of Airy Beams Impinging on Graphene-Substrate Surfaces - Fuping Wu; Yuanfei Hui; Zhiwei Cui; Ju Wang (International Journal of Optics)
In this work, we analytically and numerically investigate the reflection characteristics of the airy beams impinging on graphene-substrate surfaces. The explicit analytical expressions for the electric and magnetic field components of the airy beams reflected from a graphene-substrate interface are derived. The local-field amplitude, Poynting vector, and spin and orbital angular momentum of the reflected airy beams with different graphene structure and beam parameters are presented and discussed. The results show that the reflection properties of the airy beams can be flexibly tuned by modulating the Fermi energy of the graphene and have a strong dependence on the incident angle and polarization state. These results may have potential applications in the modulation of airy beams and precise measurement of graphene structure parameters.